The Science and Technology Program for Homemakers at the Society Learning Centre (PKBM) in Padang - Hayatunnufus Hayatunnufus; Wirdatul Aini (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2018)
This community service was because many homemakers had much free time, but they did not yet have productive activities that could help adding the family income. Therefore, they were put in a program and trained to sew bajukurung. The aim was to have the women skillfully so that they were motivated to work hard and eager to open their own sewing business. The participants of the program were 17 homemakers living at Parupuk Raya Air Tawar Barat. The methods used in the program were: a) counseling; it was to prepare the participants to have a motivation, passion and characters, b) experiment; used to train the participants to be skillful in sewing bajukurung, begin with the measurement, cutting, and then sewing. The outcomes of the programs were having the participants informed and trained, the instructors helped them and showed them ways to sew. The training had been conducted. The participants could do measurement; they could draft the patterns, cut the cloth and sew it to be bajukurung.Keywords: Science and Technologi, Homemakers, Society Learning Center